ANALYSIS OF THE THERMAL RESISTANCE OF POLYETHYLENE MODIFIED WITH COBALT ACETATE (Scientific journal of the Fergana State University, 2023)
By improving the properties of polyethylene, its materials can be used as a substitute. In this work, the modification of cobalt acetate and polyethylene was studied. Modification of polyethylene improves the physical and mechanical properties of the base polyethylene. Metal acetates significantly affected the heat resistance and impact resistance of polyethylene.